ORGANIZATIONAL AMBIDEXTERITY AND FLEXIBILITY IN SUPPLY CHAIN MANAGEMENT: REVIEW AND BIBLIOMETRIC ANALYSIS - Dian Palupi, Restuputri; Yassierli, Yassierli; Ilyas, Masudin; Nazaruddin, Malik; Evan, Lau (Inderscience Enterprises Ltd., 2023)
Researchers have been continuing to investigate sundry issues of organisational ambidexterity, particularly in the supply chain context. Organisational ambidexterity aims to help companies react successfully to the emergence of new competitors, the development of new technologies that change the industry, or sudden changes in overall market conditions. We reviewed papers on organisational ambidexterity in the supply chain literature 2012–2021 to define the problems, approaches, solutions, models, and projection. We collected published papers about supply chain organisational ambidexterity and decided on 34 to collect the data. Through graphical analysis and systematic classification, four main clusters regarding organisational ambidexterity in the supply chain have been identified as the most promising and potential future research opportunities. Our findings showed the broad knowledge to understand the main clusters of research steps in reasonable development ideas. With this insight, researchers and practitioners will soon design highly relevant and meaningful initiatives.